Cryptotanshinone from the Salvia miltiorrhiza Bunge Attenuates Ethanol-Induced Liver Injury by Activation of AMPK/SIRT1 and Nrf2 Signaling Pathways - Nagappan, Arulkumar (Int J Mol Sci, 2019)
Cryptotanshinone (CT), a diterpene that is isolated from Salvia miltiorrhiza Bunge, exhibits anti-cancer, anti-oxidative, anti-fibrosis, and anti-inflammatory properties. Here, we examined whether CT administration possess a hepatoprotective effect on chronic ethanol-induced liver injury. We established a chronic alcohol feeding mouse model while using C57BL/6 mice, and examined the liver sections with hematoxylin-eosin (H&E) and Oil Red O (ORO) staining. Further, we analyzed the lipogenesis, fatty acid oxidation, oxidative stress, and inflammation genes by using quantitative polymerase chain reaction (qPCR) and immunoblotting in in vivo, and in vitro while using HepG2 and AML-12 cells. CT treatment significantly ameliorated ethanol-promoted hepatic steatosis, which was consistent with the decreased hepatic triglyceride levels. Interestingly, CT activated the phosphorylation of AMP-activated protein kinase (AMPK), sirtuin 1 (SIRT1), and nuclear factor E2-related factor 2 (Nrf2) proteins. Importantly, compound C (AMPK inhibitor) significantly blocked the CT-mediated reduction in TG accumulation, but not Ex52735 (SIRT1 inhibitor), which suggested that CT countering ethanol-promoted hepatic steatosis is mediated by AMPK activation. Furthermore, CT significantly inhibited cytochrome P450 2E1 (CYP2E1) and enhanced both the expression of antioxidant genes and hepatic glutathione levels. Finally, CT inhibited the ethanol-induced inflammation in ethanol-fed mice and HepG2 cells. Overall, CT exhibits a hepatoprotective effect against ethanol-induced liver injury by the inhibition of lipogenesis, oxidative stress, and inflammation through the activation of AMPK/SIRT1 and Nrf2 and the inhibition of CYP2E1. Therefore, CT could be an effective therapeutic agent for treating ethanol-induced liver injury.